The pain and gain of offshoring: The effects of tax progression in a segmented labour market - Silvia Rocha-Akis (Center for Economic Studies and ifo Institute (CESifo), 2012)
Over the previous two decades, many OECD countries have lowered the degree of progressivity in their tax structures. In this paper, I investigate labour tax progression in a world characterised by a segmented labour market where the higher-paying jobs are rationed due to (i) oligopolistic market structures, (ii) insider-oriented unions and (iii) international offshoring. In this second-best world, a revenue-neutral decrease in the progressivity of the tax schedule promotes higher domestic (net-of-tax) wage inequality where a shrinking fraction of workers provides the tax revenue to finance the redistribution to an increasing share of lower-wage workers. However, as the tax reform involves an increase in the offshoring intensity, which may translate into a cost advantage for the domestic average consumer, the overall welfare effect is ambiguous. It is shown that the negative effects dominate if trade unions are sufficiently insider-oriented.
Keywords: L13; H20; F16; J50; 330; relocation; unionised oligopoly; labour market segmentation; labour income tax progression; trade union preferences; Lohnsteuer; Steuerprogression; Steuerwirkung; Lohnstruktur; Arbeitsmarktsegmentierung; Offshoring; Insider-Outsider-Modell; Gewerkschaftsmitgliedschaft; Wohlfahrtseffekt; Theorie